A new method for Synthetic Impulse and Aperture Radar transmitting waveform design based on non‐sequential positive, negative and random carrier frequency coding with dot product approach. Issue 1 (3rd October 2021) - Yaghoubi Aliabad, Pourya; Soleimani, Hossein; Soleimani, Mohammad
Abstract: Synthetic Impulse and Aperture Radar (SIAR) is a kind of Multiple Input Multiple Output (MIMO) radar. It is a four‐dimensional radar that has advantages against stealth targets, multi targets, anti‐radiated missile, reconnaissance and interference, as well as valuable features in high range resolution and high detection probability. SIAR uses special frequency coding separately in each antenna. This code has an essential function in SIAR, such as separating frequency bandwidth, satisfying orthogonality in transmitted signals, suppressing range‐angle and range‐Doppler frequency coupling. Pulse‐to‐pulse frequency code agility is a kind of radar signal coding that is used to suppress the sidelobes in range‐Doppler frequency. In this study, a design method is suggested to transmit waveform based on non‐sequential positive, negative and random carrier frequency coding with the dot product approach in pulse‐to‐pulse frequency code agility, to reduce sidelobes in range‐Doppler frequency coupling. The simulation results showed that this method could effectively remove the strong coupling between range‐Doppler frequency. Removing coupling in the range‐Doppler frequency decreases the sidelobes.